Germinação de sementes de Piptadenia moniliformis (Leguminosae) em função da salinidade, temperatura e petróleo - Santos, Drayena Alves dos (Universidade Federal Rural do Semi-Árido, 2017)
The limited availability of water negatively affects the propagation of some plant species, affecting its germination process, which is one of the most critical events in plant growth and development. This is a biological phenomenon that, physiologically, can be characterized as a resumption of embryo growth and tegmental rupture by the radicle. Another limiting factor for the propagation of these species is the salinity of the soil, the region for presenting an irregular distribution of rainfall throughout the year, it needs other tools to acquire water, the most used way of obtaining water in periods of drought is the irrigation. Since most of the water used for irrigation in small properties has high salts, due to the fact that the water sources are found in saline soils. For this reason, it is justified to carry out studies aimed at the recovery of degraded areas, seeking to know the germinative behavior of seeds of native species and their tolerance to salinized soils, as well as contaminated with oil. The objective of this work is to study the germinative response of Piptadenia moniliformis seeds, as a function of temperatures, different salt concentrations and petroleum. The following criteria were evaluated: imbibition curve as a function of time, in different saline concentrations; Germination as a function of time; Germination as a function of the (Electric Conductivity) EC, and germination as a function of time of contact with petroleum, using already established mathematical regression models. Seeds of Piptadenia moniliformis showed higher germination when they were not submitted to the water absorption process; All treatments showed high germination values, less at 40 ° C. Salinity decreases water absorption, absorption rates, germination, time required to germinate 50% of maximum germination, and time of germination rate. EC = 20 dS m-1 showed the slowest absorption in all experiments. 27.69ºC is the optimum temperature for the germination of these seeds. Oil adversely affects the emergence of Piptadenia moniliformis seeds. The treatments of 12 hours and 48 hours of oil immersion presented the greatest emergencies. The treatments T0 and T12 obtained the highest germination rates
Keywords: Absorção; Caatinga; Catanduva; Dormência; Absorption; Caatinga; Catanduva; Nullity; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE